Upgrading the Elementary Accounting Course. - Parker, William M. (The Accounting Review, 1965)
Abstract The article emphasizes the need for revision of the introductory collegiate course in accounting. Among the needed reforms is the deletion of most bookkeeping and special procedural matters, and this should, of course, be accompanied by the elimination of these subjects from textbooks and other instructional materials. For all truly basic and fundamental purposes, as perhaps many textbook writers will acknowledge, double-entry accounting requires just two kinds of records, each of which performs a distinct and readily explainable function. These are the general journal and the general ledger. It is essential that the student master the use of these two devices at the very beginning of his studies, but he will need no additional knowledge of accounting mechanics for any theoretical purposes. the ledger technique which is adopted depends upon the underlying method of keeping track of the inventory. While such underlying procedures may often receive too much emphasis in textbooks, it is with the ledger practices that the article is concerned.